2016
DOI: 10.17533/udea.iatreia.v29n4a01
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiología de Salmonella spp., Listeria monocytogenes y Campylobacter spp., en la cadena productiva avícola

Abstract: RESUMENSalmonella spp., Campylobacter spp. y Listeria monocytogenes son patógenos zoonóticos causantes de enfermedades transmitidas por alimentos asociadas al consumo de productos de origen animal contaminados. En este estudio se determinaron la prevalencia y los factores de riesgo asociados a la presencia de estos microorganismos en todos los eslabones de producción de pollos de engorde en dos empresas integradoras avícolas colombianas (EI-I y EI-II). En la EI-I, se aislaron Campylobacter spp., y Salmonella s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Enteritidis is a facultative intracellular pathogen responsible for food poisoning in humans called salmonellosis and was the most prevalent serotype (28.7%) in this study. In addition, it has been evidenced that the contamination of chickens by this pathogen, especially in carcasses, is related to the broiler chickens environment that may be contaminated, allowing the dissemination of this bacteria soon after slaughter 25,26 . In addition, contamination of chickens by this bacterial genus can also occur through the manipulators contaminated hand or contact with feces and contaminated water.…”
Section: Resultsmentioning
confidence: 99%
“…Enteritidis is a facultative intracellular pathogen responsible for food poisoning in humans called salmonellosis and was the most prevalent serotype (28.7%) in this study. In addition, it has been evidenced that the contamination of chickens by this pathogen, especially in carcasses, is related to the broiler chickens environment that may be contaminated, allowing the dissemination of this bacteria soon after slaughter 25,26 . In addition, contamination of chickens by this bacterial genus can also occur through the manipulators contaminated hand or contact with feces and contaminated water.…”
Section: Resultsmentioning
confidence: 99%
“…Among the few studies conducted in Colombia, one developed by the National Institute of Health, known in Colombia as Instituto Nacional de Salud (INS) in 2012, found a prevalence of 10.9% for Campylobacter in 19 chicken carcass processing plants [ 29 ]. Another study conducted in 2016 found a prevalence of 10% [ 30 ]. In addition, the Colombian Integrated Surveillance Program for Antimicrobial Resistance (COIPARS) has identified Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%